2017
DOI: 10.14214/sf.1657
|View full text |Cite
|
Sign up to set email alerts
|

Time consumption and productivity in manual tree felling with a chainsaw – a case study of resinous stands from mountainous areas

Abstract: Highlights• An important preoccupation in sustainable logging management is represented by the analysis of work time structure and productivity level in manual tree felling with a chainsaw.• Sound knowledge of the factors which influence work time allows better planning of harvesting operations so that deadlines could be met and damage to forest ecosystems be minimized. AbstractThe purpose of this research is to establish time consumption and productivity when using Husqvarna 365 chainsaw for resinous tree fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 12 publications
2
21
1
Order By: Relevance
“…Therefore, as can be seen in Figure 3 Tree size is one of the main characteristics influencing tree felling and processing with a chainsaw. The time consumed for the primary processing of felled trees increased as a function of the stem size [26]. Most studies use dbh as the main factor for estimating the productivity and work time by either linear equations [25,33,47,48] or the power function [27,49] and stump diameter in an exponential model [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, as can be seen in Figure 3 Tree size is one of the main characteristics influencing tree felling and processing with a chainsaw. The time consumed for the primary processing of felled trees increased as a function of the stem size [26]. Most studies use dbh as the main factor for estimating the productivity and work time by either linear equations [25,33,47,48] or the power function [27,49] and stump diameter in an exponential model [24].…”
Section: Resultsmentioning
confidence: 99%
“…Tree delimbing and cross-cutting in the felling area take more time than felling itself. In the felling area analysed in this study, 1 m 3 of wood was felled in 316.5 s (the felling operation was studied using a similar methodology under similar working conditions and the results were presented in a previous article) [26], while the delimbing and cross-cutting of 1 m 3 of wood took 536.32 s. [25] showed that delimbing and cross-cutting accounted for 43.98% of the felling operation (2.01 min•tree −1 and 4.57 min•tree −1 , respectively). [27] showed that felling took approximately 20% of the productive work time, and delimbing took 46% of the productive work time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working time structure has been studied by numerous researchers, because working time consumption depends on many factors. Câmpu and Ciubotaru [34] and Ciubotaru and Câmpu [35] studied timber harvesting using chainsaws in Carpathian mountain stands. Wójcik and Petrów [36] investigated the impact of loggers' experience on productivity and labour consumption during the harvesting of timber from mature stands.…”
Section: Introductionmentioning
confidence: 99%
“…cutting efficiency) and duration of felling, and cross-cutting in motor-manual operations using chainsaws (e.g. Câmpu and Ciubotaru 2017;Marenče et al 2017;Ciubotaru and Câmpu 2018). However, only a limited number of studies are available on mechanised harvesting using CTL harvesters.…”
Section: Introductionmentioning
confidence: 99%